Data modelling of converters for the automation and monitoring of MTDC grids. Issue 3 (19th June 2019) - Roy, Gaurav Kumar; Hu, Jingxin; Sadu, Abhinav; Ponci, Ferdinanda; Monti, Antonello; De Doncker, Rik W.
Abstract : Multi‐terminal DC (MTDC) grids based on voltage source converters (VSCs) are a promising option to integrate the increasing share of generation from the distributed energy resources (DERs) both in the transmission and distribution grids. However, with the broader use of VSCs for the transmission and distribution grid, there is an absence of a standardised data model for the VSC. In this work, the authors propose an IEC 61850 based data model for VSCs and an existing IEC 61850 model is extended for the dual‐active bridge (DAB) converter as an interlink between various DC terminals and the modular multilevel converter (MMC). Furthermore, a generic data modelling guideline is proposed for intelligent electronic devices (IEDs), which are responsible for the interoperability among converters in the MTDC grid. The implementation of the real‐time monitoring system of a hybrid AC‐DC MTDC grid with the proposed IED is presented as an exemplary case. Through experimental tests of this MTDC grid, it is shown that the proposed IED meets the latency requirements for P2 through P6 class of monitoring, protection, and control applications according to the IEC 61850 standard. The automation architecture presented in this work is also validated for interoperability within the MTDC grid.